Risky neighborhoods? House appreciation in underserved areas - Roberto G. Quercia; Ayse Can; George W. McCarthy (European Regional Science Association (ERSA), 1998)
This research project will investigate house price appreciation trends in traditionally underserved areas. The primary goal is to develop and test a methodology to determine what part of a home (appreciation)is due to structural and neighborhood effects, and what part may be attributable to other factors such as homeowners actions (including repair, maintenance, and upgrades). We will employ a space-time modeling framework to measure appreciation varying influences of structural and neighborhood, and other factors on appreciation overtime. We will compare appreciation trends across different submarkets (underserved and conventional) and for both high risk and low risk borrowers. The empirical analysis will employ thr TRW-REDI housing transaction data set for Miami MSA (USA) for the 1985-1993 period in conjunction with Census and American Housing Survey (AHS) data.
Keywords: 330